(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article presents a scholarly analysis of the role of Qur’ anic recitations (qira’ at) in the exegesis (tafsir) of the Holy Qur’ an. The science of Qur’ anic recitations holds a distinctive position within the Islamic scholarly tradition and constitutes one of the fundamental sources for the discipline of Qur’ anic exegesis. This study examines how variant recitations expand the semantic scope of Qur’ anic verses, their influence on jurisprudential rulings (fiqhi ahkam), and the methodological approaches employed by classical exegetes (mufassirun) in utilizing these variant readings. The findings indicate that the majority of recitation variants are complementary in nature, collectively demonstrating the richness of Qur’ anic meanings. The study conducts a comparative analysis based on the works of al-Ṭabari, al-Zamakhshari, Ibn al-Jazari, and contemporary scholars.